Characterization of a genomic Island carrying the tet(X4) gene in porcine Acinetobacter towneri co-harboring plasmid-borne blaNDM−1 and blaOXA−58 genes - Li, Aijuan; Yu, Runhao; Zhao, Wenbo; Schwarz, Stefan; Li, Chenglong; Yao, Hong; Du, Xiang-Dang (Frontiers in Veterinary Science, 2022)
Tigecycline and carbapenems are last-resort antimicrobial agents to treat serious infections caused by multi-drug resistant bacterial pathogens. However, the co-occurrence of tigecycline and carbapenem resistance determinants challenges the clinical efficacy of these antimicrobial agents. In this study, we report the co-existence of tet(X4), blaNDM-1 and blaOXA-58 genes in the porcine Acinetobacter towneri isolate 19110F47. Sequence analysis revealed that tet(X4) gene, along with the florfenicol resistance gene floR, was flanked by three copies of IS91-like elements, which can form three different translocatable units (TUs), and were located in a 41,098-bp multidrug resistance region (MDRR) within a novel 100,354-bp genomic island (GI) region. TUs comprising floR-virD2-ISVsa3, hp-abh-tet(X4)-ISVsa3 and virD2-floR-ISVsa3-hp-abh-tet(X4)-ISVsa3 can be looped out from the chromosomal DNA and facilitate the transfer of the TU-based resistance genes into other plasmidic or chromosomal sites. In addition, the carbapenemase genes blaNDM-1 and blaOXA-58 were found on different non-conjugative multiresistance plasmids in this isolate, with the genetic contexts ISAba125-blaNDM-1-bleMBL-tnpR and ΔISAba3-blaOXA-58-ISAba3, respectively. The simultaneous occurrence of tet(X4), blaNDM-1 and blaOXA-58 in the same porcine A. towneri isolate emphasizes the importance of antimicrobial resistance surveillance in food-producing animals.